Platelet parameters in hepatic hydatid cysts - GÜLALİ AKTAŞ (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Hepatic cyst hydatid infection is caused by microorganisms named echinococcus which belong to family Taenidae. Platelets are considered as a mediator in inflammation and infectious diseases because of the various  proinflammatory substances that they contain.